PENGEMBANGAN MODEL PEMBELAJARAN "ACTIVE LEARNING" DENGAN METODE KELOMPOK UNTUK MENINGKATKAN KUALITAS PROSES PEMBELAJARAN DI PERGURUAN TINGGI: Studi pada Mata Kuliah Strategi Pembelajaran di LPTK. - Muhtadi, Ali (2010)
This research departed from the low quality of teaching learning process in Institutes of Education Workforce Education. In general, learning process in the institutions has not been capable in optimizing students' participation in the interaction process of the lectures. This research aimed at producing an effective "active learning" model to improve the quality of the learning process of learning strategies subject in Institutes of Education Workforce Education, especially in regards with students' participation in the interaction process during lectures. The research employed Research and Development (R & D) method consisting of three stage; they are preliminary study, model development, and model validation. The preliminary study covered two parts: literature study and field survey. The development stage involved three parts: first draft composition, limited-scale try out and large-scale try out. Meanwhile, the third stage was an experiment to test the validity of the resulted product. The experiment was a quasi experimental design using pretest-posttest-control group design. The subjects of this research were lecturers and students who attended learning Strategies subject in four Institutes of Education Whorkforce Education in Yogyakarta; they are UNY, UAD, UPY, and UST. The data were collected through questionnaires, interview, observation, test, and document analysis. The data analysis technique employed qualitative and quantitative techniques. Based on the theoretical study and field study results which were buttressed with the results of limited-scale try out and large-scale try out, an appropriate learning model was produced to improve the learning process quality in terms of students' participation in the interaction process during the Lecture of Learning Strategies subject in four Institutes of Education Whorkforce Education, which is an active learning model with grouping method. The development of this learning model was based on the concept of brain-performance-based learning theories, constructivist theories, and collaborative/ cooperative learning theories. The resulted model consisted of three parts: planning model, implementation model (orientation, shaping and team assignment, exploration, learning to be expert team, reorientation, team presentation, understanding checking, reflection and conclusion, and formative evaluation), and learning model evaluation. The results of the experiment and validation of the learning model showed that: (1) there were quantitative improvements among students who were actively involved in the learning interaction process; (2) there were improvements in the students' average scores of achievement; there was significant difference between the scores before and after the treatment using active learning with grouping method in the process during the lecture of Learning Strategies; (3) the resulted learning model was better in improving the number of students who actively participated in the learning process than the learning model that the lecturers used to apply in the class; and (4) the resulted learning model was better in improving the average scores of the students than the previous learning model used by the lecturers with significant differences. Based on the findings, it is recommended that lecturers of Institutes of Education Workforce Education use this learning model